PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NUSA NIPA - Laurensiana Ngguwa Modhe; Yosefina Andia Dekrita; Kristiana Reinaldis Aek (Jurnal Projemen UNIPA, 2026)
This study aimed to: (1) describe the financial literacy, lifestyle, and financial behaviour of students in the Management Study Program at the Faculty of Economics and Business, Nusa Nipa University; and (2) analyse the partial and simultaneous influences of financial literacy and lifestyle on financial behaviour. Descriptive analysis results indicate that financial literacy falls into the "good" category (72%), lifestyle falls into the "fairly good" category (66%), and financial behaviour falls into the "good" category (70%). Furthermore, t-test results demonstrate that financial literacy has a positive and significant partial effect on financial behaviour. Similarly, lifestyle also exerts a positive and significant effect on financial behaviour. The F-test results reveal that financial literacy and lifestyle simultaneously have a significant effect on financial behaviour. Finally, the coefficient of determination analysis shows that these two independent variables explain 44.4% of the variance in the financial behaviour of the management students, while the remaining 55.6% is influenced by other variables outside the scope of this study.